ANALISIS KEEFEKTIFAN BUKU FOTO SEBAGAI MEDIA INFORMASI MINUMAN HERBAL UNTUK GENERASI Z DI KOTA BATAM - Celine Te; Deli Deli (Narada : Jurnal Desain dan Seni, 2022)
Books are one of the information media that is still used today because it can be used anytime and anywhere because its use does not require a special way. Jamu is one of the Indonesian culture that is in line with the development of the times. Due to the development of drugs in the medical world, the role of herbal medicine as an herbal drink and medicines began to be forgotten. Therefore the author will design a photo book containing new or unknown information content about herbal medicine. In this study the author uses the MDLC (Multimedia Development Life Cycle) method and the R&D (Research and Development) method. Both of these methods consist of several stages of preparation, namely determining the potential and problem which at this stage the writer will determine the concept and design of the photo book, the next stage is the collection of data which at this stage the author will gather information and photos that will later become content From the contents of the photo book, the next stage is the design of the product at this stage the writer will design a photo book in accordance with the data that has been collected, the final step is to do the effectiveness testing of the photo books on a small and large scale. The distribution of the questionnaire was carried out on generation Z in Batam City, with a quantitative analysis obtained the results of the photo book assessment were feasible (scale of 4.01 of 5) as a medium for disseminating information.